2006
DOI: 10.1007/s00012-006-2005-x
|View full text |Cite
|
Sign up to set email alerts
|

Permutation representations of left quasigroups

Abstract: The concept of a permutation representation has recently been extended from groups to quasigroups. Following a suggestion of Walter Taylor, the concept is now further extended to left quasigroups. The paper surveys the current state of the theory, giving new proofs where necessary to cover the general case of left quasigroups. Both the Burnside Lemma and the Burnside algebra appear in this new context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The category Q̲̲0.16em fin of finite Q ‐ sets is the full subcategory of IFSQ induced on the class of finite Q ‐sets. (Note that the alternative definitions here agree with the earlier definitions of [, ] — compare [, Th. 5.4].…”
Section: Iterated Function Systemssupporting
confidence: 80%
See 1 more Smart Citation
“…The category Q̲̲0.16em fin of finite Q ‐ sets is the full subcategory of IFSQ induced on the class of finite Q ‐sets. (Note that the alternative definitions here agree with the earlier definitions of [, ] — compare [, Th. 5.4].…”
Section: Iterated Function Systemssupporting
confidence: 80%
“…A Q ‐IFS is said to be a basic Q ‐ set if it is a homomorphic image of a homogeneous space PQ for a subquasigroup P of Q — compare Definition (a). Each basic Q ‐set is irreducible in the sense that it has no proper, nonempty subobjects , Cor. 8.2].…”
Section: Iterated Function Systemsmentioning
confidence: 99%
“…ε-crisp coalgebras. In [10], Smith defines a Q-iterated function system (Q-IFS) as a Q-indexed family of stochastic linear maps on a vector space R(X). Since each linear map is determined by its restriction as Set-map α : X → R(X), a stochastic linear map is given by any mapping from X to the set of probability distributions on X, that is as a coalgebra of type D(X).…”
Section: Membership Through Constant Coalgebrasmentioning
confidence: 99%
“…Now the case of [10] is captured easily, as ε X : I Q → D Q where ε X (τ )(q) = τ (q), which inherits from x →x the property of being mono, natural, and sub-cartesian.…”
Section: Membership Through Constant Coalgebrasmentioning
confidence: 99%
“…There are some attempts to study permutation representations of quasigroups and loops-algebraic structures that are a generalization of groups. For instance, Jonathan Smith has intensively studied quasigroup and loop representations in a series of papers [9][10][11]. Also, the study of sharply transitive sets in quasigroup actions can be found in [7].…”
Section: Introductionmentioning
confidence: 99%